Problems of Crimes Against Humanity and Tools for Development of Officer’s Skills on Conflict Prevention Missions. GAP - Gaming for Peace Project - Nowak, Alexandra (Kriminalističke teme, 2018)
We are living in very diverse word. We meet a lot of people from different cultures and religions in our private life and on duty. The world is becoming more and more biased and radicalized. Gaming for Peace (GAP project) is a project funded through the European Commission Horizon 2020 Securities programme. GAP is developing a new curriculum in soft skills for instance communication, cooperation, empathy and understanding and gender awareness and cultural competency for personnel deployed in peacekeeping missions.